2006
DOI: 10.1108/13665620610682071
|View full text |Cite
|
Sign up to set email alerts
|

Mentor or evaluator? Assisting and assessing newcomers to the professions

Abstract: PurposeA four‐year longitudinal study was conducted on the school‐to‐work transition in four professions traditionally called “helping professions,” namely education, social work, occupational therapy, and physiotherapy. One goal of the study was to understand the nature and process of the mentoring relationships that develop and sustain newcomers in their professional life, especially the possible tension between the roles of mentor and evaluator. It was expected that this would help us in our jobs of prepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…• Uses feedback from mentor with critical reflection to determine their own progress (Le Maistre et al, 2006). While this review did not find any studies that focussed specifically on the interconnectedness of mentor and mentee roles, Figure 5 summarises how mentor and mentee roles mesh.…”
Section: Assessormentioning
confidence: 99%
See 3 more Smart Citations
“…• Uses feedback from mentor with critical reflection to determine their own progress (Le Maistre et al, 2006). While this review did not find any studies that focussed specifically on the interconnectedness of mentor and mentee roles, Figure 5 summarises how mentor and mentee roles mesh.…”
Section: Assessormentioning
confidence: 99%
“…The mentoring literature reflects the viewpoint that mentoring roles change as the relationship evolves (Bullough et.al., 2003;Kostovich & Thurn, 2006;Lai, 2005 ;Le Maistre et al, 2006;Rajuan, Beijaard & Verloop, 2007). Bouquillon, Sosik & Lee (2005, p.239) have concluded that 'mentoring relationships are dynamic phenomena that evolve over time and in distinct phases'.…”
Section: Other Influences On the Roles Of Mentors And Menteesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to studies (Hall et al 2008;Hawkey, 2006;Le Maistre, Boudreau & Pare, 2006;Schwille, 2008), mentors can provide not only pedagogical guidance, emotional support and professional socialization, but also empathy and serve as role models. Considering that teachers' knowledge and skills are event-structured, context-based, and practice-oriented in nature (Kessels & Korthagen, 1996), mentor teachers have multiple roles.…”
Section: The Role Of Mentor Teachermentioning
confidence: 99%